Tuberculous pleural effusion. Issue 10 (16th August 2019) - Shaw, Jane A.; Diacon, Andreas H.; Koegelenberg, Coenraad F.N.
ABSTRACT: Tuberculous effusion is a common disease entity with a spectrum of presentations from a largely benign effusion, which resolves completely, to a complicated effusion with loculations, pleural thickening and even frank empyema, all of which may have a lasting effect on lung function. The pathogenesis is a combination of true pleural infection and an effusive hypersensitivity reaction, compartmentalized within the pleural space. Diagnostic thoracentesis with thorough pleural fluid analysis including biomarkers such as adenosine deaminase and gamma interferon achieves high accuracy in the correct clinical context. Definitive diagnosis may require invasive procedures to demonstrate histological evidence of caseating granulomas or microbiological evidence of the organism on smear or culture. Drug resistance is an emerging problem that requires vigilance and extra effort to acquire a complete drug sensitivity profile for each tuberculous effusion treated. Nucleic acid amplification tests such as Xpert MTB/RIF can be invaluable in this instance; however, the yield is low in pleural fluid. Treatment consists of standard anti‐tuberculous therapy or a guideline‐based individualized regimen in the case of drug resistance. There is low‐quality evidence that suggests possible benefit from corticosteroids; however, they are not currently recommended due to concomitant increased risk of adverse effects. Small studies report some short‐ and long‐term benefit from interventions such as therapeutic thoracentesis, intrapleural fibrinolytics and surgery but many questions remain to be answered.